KOMUNIKASI INTERPERSONAL DAN FASILITAS KESEHATAN SERTA PENGARUHNYA TERHADAP KEPERCAYAAN DAN WOM PADA RUMAH SAKIT UMUM DAERAH KOTA MATARAM - Nurul Indah Wijayanti (Master of Management, Mataram University, 2015)
This research examined the influence of interpersonal communication, medicalfacilities, trust and word of mouth (WOM) outpatients in Mataram City Hospital.Specifically, the objectives of this research was to determine the significance effect of theinterpersonal communication and medical facilities toward the trust and WOM outpatientsin Mataram City Hospital. The samples using purposive sampling method. Respondentswere public patients undergoing outpatient treatment and patients who had more than twotimes in poly Mataram City Hospital. This research uses the path analysis with theapplication Statistical Product and Service Solutions (SPSS). The results showed thatinterpersonal communication positive and significant effect toward the trust, medicalfacilities positive and significant effect toward the trust, interpersonal communicationpositive and significant effect toward WOM, medical facilities are not exhibited significantlypositive effect toward WOM, trust were positive and significant effect toward WOM,interpersonal communication positive and significant effect toward WOM through trust, aswell as medical facilities significant and positive effect toward WOM through trustoutpatients in Mataram City Hospital.Keywords: Interpersonal Communication, Medical Facilities, Trust,and Word Of Mouth(WOM).